2012
DOI: 10.1097/dbp.0b013e3182475267
|View full text |Cite
|
Sign up to set email alerts
|

Severity of the Aggression/Anxiety-Depression/Attention Child Behavior Checklist Profile Discriminates Between Different Levels of Deficits in Emotional Regulation in Youth With Attention-Deficit Hyperactivity Disorder

Abstract: Objective We examined whether severity scores (1SD vs. 2SDs) of a unique profile of the Child Behavior Checklist (CBCL) consisting of the Anxiety/Depression, Aggression, and Attention (A-A-A) scales would help differentiate levels of deficits in children with ADHD. Study Design Subjects were 197 children with and 224 without ADHD. We defined deficient emotional selfregulation (DESR) as an aggregate cut-off score of >180 but <210 (1SD) on the A-A-A scales of the CBCL (CBCL-DESR) and Severe Dysregulation as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
86
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(98 citation statements)
references
References 20 publications
10
86
1
1
Order By: Relevance
“…These findings are consistent with studies that reported that severe forms of emotional dysregulation defined through marked elevations in specific scales of the CBCL predicted both lifetime and current diagnosis of bipolar disorder in youth with ADHD (Faraone et al, 2005;Uchida et al, 2014). Biederman et al (2009bBiederman et al ( , 2012 also found that a positive CBCL severe emotional dysregulation profile predicted a subsequent diagnosis of bipolar disorder, impaired psychosocial functioning and higher risk of psychiatric hospitalization in youth with ADHD followed prospectively into young adult years. Even less severe forms of deficits in emotional regulation have been associated with manic switches in ADHD children with MDD (Biederman et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with studies that reported that severe forms of emotional dysregulation defined through marked elevations in specific scales of the CBCL predicted both lifetime and current diagnosis of bipolar disorder in youth with ADHD (Faraone et al, 2005;Uchida et al, 2014). Biederman et al (2009bBiederman et al ( , 2012 also found that a positive CBCL severe emotional dysregulation profile predicted a subsequent diagnosis of bipolar disorder, impaired psychosocial functioning and higher risk of psychiatric hospitalization in youth with ADHD followed prospectively into young adult years. Even less severe forms of deficits in emotional regulation have been associated with manic switches in ADHD children with MDD (Biederman et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…20,42 The high rates of mood dysregulation in the ADHD + CBCL-AT children are also consistent with an emerging body of literature documenting high rates of mood disorders in children with ASDs. 43 Further research is needed to better understand the role ATs confer on emotion regulation in children with ADHD.…”
Section: E618supporting
confidence: 65%
“…Two subscales were created from the CBCL by summing the anxiety/ depression, aggression, and attention scales (severe dysregulation: sum of T scores $210; deficient emotional selfregulation: sum of T scores of 180-210). 20 Psychosocial functioning was assessed by using the Social Adjustment Inventory for Children and Adolescents (SAICA). 21 Using methodology recommended by Reynolds 22 and used previously by this team, 23 we identified children who were socially disabled on the basis of the discrepancy between the expected SAICA scaled score (derived from the estimated Full Scale IQ) and the actual SAICA scaled score.…”
Section: Assessment Proceduresmentioning
confidence: 99%
“…27 The CBCL has been shown to discriminate between different levels of emotional dysregulation in attention deficit hyperactivity disorder (ADHD), but with greater success in those defined as having severe dysregulation. 31 The sensitivity of the CBCL seems greatest when the behaviors are more extreme. This is consistent with our proposed explanation that the low rate of parental identification of attention problems was the result of an inability to observe the inattentive (subtle) behaviors that predominated in children with CAE.…”
Section: Statistical Analysis Baseline Neurocognitive Test Results Amentioning
confidence: 99%